2006
DOI: 10.21273/jashs.131.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Changes in Cantaloupe during Growth, Maturation, and in Stored Fresh-cuts Prepared from Fruit Harvested at Various Maturities

Abstract: A likely reason why consumers are not repeat buyers of many fresh-cut fruit is inconsistent or unsatisfactory flavor and/or textural quality. Research toward understanding mechanisms responsible for generation, and/or loss of flavor compounds in fresh-cut fruit is limited. Solid phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS) were utilized to study flavor volatile profiles in anthesis-tagged cantaloupe (Cucumis melo L. var. reticulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
118
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 80 publications
(78 reference statements)
17
118
3
2
Order By: Relevance
“…In this collection, aldehydes are present in between 15-40% relative levels of the total aroma of the profile, and hexanal shows the highest relative content with respect to other aldehydes, in agreement with previous results working with PS and other non-climacteric NILs with introgression in LG III (Obando-Ulloa et al, 2008). Hexanal is considered to contribute to green notes and, secondarily, to melon aroma, and benzaldehyde has been defined as a pleasant aroma for Cantaloupe type melons (Beaulieu, 2006;Beaulieu & Grimm, 2001), and high concentrations are usually associated with a high degree of melon ripening (Beaulieu & Grimm, 2001). Also, it is not unlikely that the unsaturated aldehyde fraction and, particularly, hexanal, may be due to lipid peroxidation during sampling and freezing (Ma et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this collection, aldehydes are present in between 15-40% relative levels of the total aroma of the profile, and hexanal shows the highest relative content with respect to other aldehydes, in agreement with previous results working with PS and other non-climacteric NILs with introgression in LG III (Obando-Ulloa et al, 2008). Hexanal is considered to contribute to green notes and, secondarily, to melon aroma, and benzaldehyde has been defined as a pleasant aroma for Cantaloupe type melons (Beaulieu, 2006;Beaulieu & Grimm, 2001), and high concentrations are usually associated with a high degree of melon ripening (Beaulieu & Grimm, 2001). Also, it is not unlikely that the unsaturated aldehyde fraction and, particularly, hexanal, may be due to lipid peroxidation during sampling and freezing (Ma et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The results of the volatile analyzes were expressed as percentage of total chromatographic area of the 28 volatile compounds of the profile reported in Table 2 (Muriel, Antequera, Petrón, Andrés, & Ruiz, 2004). These compounds were recovered and positively identified within the run time (Beaulieu, 2005(Beaulieu, , 2006Muriel et al, 2004). Table 1 Mean relative content of the probable aromatic compounds identified in the headspace of the fruit of the collection of near-isogenic lines (NILs) of melon and the parental line 'Piel de sapo' (PS).…”
Section: Juice Sampling For Aroma Volatile Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, many volatile analytes in the vapour phase of this kind of sample are often present in too low concentrations (Beltran et al, 2006). Beaulieu and Grimm (2001) and Beaulieu (2006b) extensively analysed melon aroma using solid-phase microextraction (SPME), reporting and verifying 25 of the aforementioned compounds for the first time in cantaloupe melons. Since then, several studies reported SPME as a good semi-quantitative methodology for the determination of volatile organic compounds (VOCs) in several vegetal samples including muskmelon (Kourkoutas et al, 2006;Verzera et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Until now, around 300 volatile compounds have been identified in muskmelon and watermelon samples (Beaulieu & Grimm, 2001;Beaulieu & Lancaster, 2007;Beaulieu & Lea, 2006;Beaulieu, 2006aBeaulieu, , 2006bHomatidou, Karvouni, Dourtoglou, & Poulos, 1992;Itrat, 2006;Jordán, Shaw, & Goodner, 2001;Kourkoutas, Elmore, & Mottram, 2006;Liu et al, 2012;Obando-Ulloa & Moreno, 2008;Obando-Ulloa & Ruiz, 2010;Perry, Wang, & Lin, 2009;Saftner, Abbott, Lester, & Vinyard, 2006;Verzera, Dima, Tripodi, & Ziino, 2011). Due to the important role of volatile components in organoleptic quality of foods and beverages, these compounds have been widely studied and analytical methodologies for their determination in fruit matrices are continuously being developed, including both GC (Beaulieu, Ingram, Lea, & Bett-Garber, 2004;Beaulieu & Lancaster, 2007;Beaulieu & Lea, 2006;Gonda et al, 2010;Kemp, 1975;Kourkoutas et al, 2006;Liu et al, 2012) and GC-O (Jordán et al, 2001;Lignou, Parker, Baxter, & Mottram, 2014) …”
Section: Introductionmentioning
confidence: 99%